If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2y + -9 + 3 = y Reorder the terms: -9 + 3 + 2y = y Combine like terms: -9 + 3 = -6 -6 + 2y = y Solving -6 + 2y = y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-1y' to each side of the equation. -6 + 2y + -1y = y + -1y Combine like terms: 2y + -1y = 1y -6 + 1y = y + -1y Combine like terms: y + -1y = 0 -6 + 1y = 0 Add '6' to each side of the equation. -6 + 6 + 1y = 0 + 6 Combine like terms: -6 + 6 = 0 0 + 1y = 0 + 6 1y = 0 + 6 Combine like terms: 0 + 6 = 6 1y = 6 Divide each side by '1'. y = 6 Simplifying y = 6
| 4+10y-1=7y+27-3y | | x=4+2.333333333y | | 3y-5=20 | | -5n-8(1+7n)=-8n | | F(x)=0.25x^2 | | h(2-5x)=2(2-hx)-5 | | 8=v-u | | 10x^3-610x=0 | | Y=-3x^2-30x-70 | | Y=-3x^2-30x-7 | | 4+24x=22 | | 4c+18=7c | | 0.7(h-2)+1.6=17 | | 27=6(-n+2)-(5-2n) | | 15xy-18x=0 | | 4+24x=72 | | 2.6x+3.8=-4.3 | | 4+6(w+3)=4(w-3) | | X^2+5m-20=0 | | 4a^2+12a-16=0 | | 4-2(x+3)=-8x-14 | | 9x+3-3x=2(3x+1) | | 549=x^2 | | y=90x+50 | | v-30=90 | | 95=9x+x | | y=90x+15 | | 5y=x+y | | X+y+3z=35 | | 1.6x=3 | | 2n%43= | | 3x=.6 |